2007
DOI: 10.1002/eqe.719
|View full text |Cite
|
Sign up to set email alerts
|

Failure of masonry arches under impulse base motion

Abstract: Recent seismic events have caused damage or collapse of invaluable historical buildings, further proving the vulnerability of unreinforced masonry (URM) structures to earthquakes. This study aims to understand failure of masonry arches-typical components of URM historic structures-subjected to horizontal ground acceleration impulses. An analytical model is developed to describe the dynamic behaviour of the arch and is used to predict the combinations of impulse magnitudes and durations which lead to its collap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 19 publications
7
117
0
Order By: Relevance
“…The blocks are separated by joint interfaces, along which the blocks can detach or slide without limit on relative displacement or rotation. Because of these features, DEM is particular suitable for analysing the dynamic behaviour of rocking masonry structures; past studies include investigation of the seismic behaviour of single blocks or block assemblages [21,22,25], masonry arches [23,24], masonry facades [25,26], free-standing columns [27,28] and entire historical structures [29,30].…”
Section: Discrete Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The blocks are separated by joint interfaces, along which the blocks can detach or slide without limit on relative displacement or rotation. Because of these features, DEM is particular suitable for analysing the dynamic behaviour of rocking masonry structures; past studies include investigation of the seismic behaviour of single blocks or block assemblages [21,22,25], masonry arches [23,24], masonry facades [25,26], free-standing columns [27,28] and entire historical structures [29,30].…”
Section: Discrete Element Modellingmentioning
confidence: 99%
“…[23,24,27,28]). The initial portion of the strong ground motion response of models was found to be rather insensitive to the damping level [27,28] while continued strong shaking and the reduction in amplitude of the free vibration can be sensitive to the damping [27].…”
Section: Sensitivity To the Chosen Damping Levelmentioning
confidence: 99%
“…In these studies, the initial hinge locations were found by static analysis, and were then assumed to reflect when the arch returns to its initial position. Despite being a single degree of freedom mechanism, the analytical model proved to effectively predict global collapse when compared to both computational discrete element modeling [12] and experimental [13] results. Regardless, the aim of this study is again to determine if this complicated four-hinge mechanism can be effectively described by an equivalent single rocking block.…”
Section: The Masonry Archmentioning
confidence: 99%
“…(9), and the ground acceleration ( g u g  ) required for uplift of the linearized system is described by Eqn. (12). Again it is useful to quantify the error associated with the linearization, which is done using the procedures described in §3.1.…”
Section: The Masonry Archmentioning
confidence: 99%
“…In addition, the limitations of existing sensing solutions, mainly related to their small sizes in comparison to the structure being monitored in addition to their short durability and difficult logistics (including power and wiring to data acquisition systems) further complicate large-scale deployments. Of interest are masonry structures, which are difficult to monitor due to inherent complexity in their behavior from the significant material non-linearity, as well as possible failures modes that can occur either locally or globally 4,5 .…”
Section: Introductionmentioning
confidence: 99%